Connecting Workshops in Digital Education - Thestrup, Klaus (Proceedings of the International Conference on Networked Learning, 2024)
Communication, production, experiments and play in networked learning can be so much more than just having meetings on Zoom or Teams. This text sketches out some possibilities and ways of understanding this. The text is organized in three parts based on both finished research and ongoing research since 2004. The first part presents an overall pedagogical framework in the form of a media ecology of communication and production between schools or pre-schools. The second part has to do with how a group of children and teachers can understand themselves as an experimenting community in open laboratories. Finally the third part sketches out how the actual ways of communication and production can take place in different forms of common synchronous and asynchronous workshops.